2014
DOI: 10.1016/j.ymssp.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Statistic-based spectral indicator for bearing fault detection in permanent-magnet synchronous machines using the stator current

Abstract: In this paper, an original method for bearing fault detection in high speed synchronous machines is presented. This method is based on the statistical process of Welch's periodogram of the stator currents in order to obtain stable and normalized fault indicators. The principle of the method is to statistically compare the current spectrum to a healthy reference so as to quantify the changes over the time. A statistic-based indicator is then constructed by monitoring specific harmonic family. The proposed metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Comparatively, the threshold scheme proposed in this paper has shown to be reliable and has the ability to make decisions independent of environmental noise and motor operating points. Thus, for real time condition monitoring applications, the proposed threshold scheme in this paper is more suitable as compared to the method as reported in [53].…”
Section: Comparison Of the Developed System With Previous Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Comparatively, the threshold scheme proposed in this paper has shown to be reliable and has the ability to make decisions independent of environmental noise and motor operating points. Thus, for real time condition monitoring applications, the proposed threshold scheme in this paper is more suitable as compared to the method as reported in [53].…”
Section: Comparison Of the Developed System With Previous Studiesmentioning
confidence: 98%
“…The threshold system as reported in [53] was designed based on the t-test table of standard deviations of the healthy and faulty motor. They consider the impact of speed variation on the decision making system.…”
Section: Comparison Of the Developed System With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…William Liu et al analyzed the EDM, wrinkling and its characterization methods caused by bearing current [7]. A. Picot think that high frequency current through the bearings lead to premature failure of the bearing, proposed the Welch cycle statistical method based on a stator current [8]. However, there are few studies on the damage mechanism, damage form and rule of bearing current, and for high-power motors such as wind turbines, bearing current damage has become the main form of mechanical damage, which needs to be studied deeply.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12]. Bearing faults though not quite common in large SMs are matter of importance [13] for high-speed machines. Demagnetization faults draw attention of research community those are found in permanent magnet synchronous machines (PMSM) [14].…”
Section: Introductionmentioning
confidence: 99%